Histamine Content In Processed Bullet Tuna (Auxis thazard) Stew With Various Concentration Of NaCl - Hattu, Nikmans; Telussa, Ivonne; Fransina, Eirene G.; Seumahu, Cecelia A. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2014)
Analysis of histamine content in processed bullet tuna (Auxis thazard) stew flesh can be carried out by Spectrophotometry method, using p- phenildiazonium sulfonate reagent. A qualitative, visual comparison of colour intensity of samples with reference colour scale of the standard solution concentration can be used to determine levels of histamine without the aid of a spectrophotometer. The histamine content is determined quantitatively by the standard curve regression equation (y= 0.003x–0.062) with determination coefficient value (R2= 0.938). The results showed that histamine content inprocessed bullet tuna (Auxis thazard) obtained: 46.9964; 40.3093; 34.4348; 28.9900 and 24.8862 mg/100g fish, at 0.5; 1.0; 1.5; 2.0 and 2.5% concentration of NaCl, respectively.